Response of EGFR-mutated pulmonary pleomorphic carcinoma to pembrolizumab - Yuki Hatakeyama; Hidenori Mizugaki; Noriyuki Yamada; Yasushi Mizukami; Ken Kuwahara; Hajime Asahina; Hirofumi Adachi; Hiroshi Yokouchi; Yoshihiro Matsuno; Satoshi Oizumi (Respiratory Medicine Case Reports, 2025)
Pulmonary pleomorphic carcinoma (PPC) is a rare and aggressive lung malignancy with limited treatment options. While immune checkpoint inhibitors (ICIs) have shown promise in treating PPC, evidence regarding their efficacy in epidermal growth factor receptor (EGFR)-mutated cases remains scarce. We report a case of a woman in her 70s diagnosed with PPC harboring EGFR L858R + E709K mutations and high expression (95 %) of programmed death-ligand 1 (PD-L1). After relapsing from concurrent chemoradiotherapy for a Pancoast tumor, the patient received osimertinib as second-line therapy. Despite an initial response, rapid disease progression necessitated left lower lobectomy, confirming PPC diagnosis. Subsequent treatment with pembrolizumab achieved notably tumor response. Although Grade 3 immune-related colitis developed, it was successfully managed with prednisolone, allowing completion of six courses of pembrolizumab. This case demonstrates the potential efficacy of ICIs in EGFR-mutated PPC, even after epidermal growth factor receptor -tyrosine kinase inhibitor (EGFR-TKI) failure and highlights the importance of appropriate adverse event management. Our findings suggest that ICIs may be a viable treatment option for EGFR-mutated PPC patients, particularly those with high PD-L1 expression.